Rhodium-catalyzed intermolecular chelation controlled alkene and alkyne hydroacylation: synthetic scope of beta-S-substituted aldehyde substrates. - Willis, M; Randell-Sly, H; Woodward, R; McNally, S; Currie, G (2006)
The use of beta-S-substituted aldehydes in rhodium-catalyzed intermolecular hydroacylation reactions is reported. Aldehydes substituted with either sulfide or thioacetal groups undergo efficient hydroacylation with a variety of electron-poor alkenes, such as enoates, in Stetter-like processes and with both electron-poor and neutral alkynes. In general, the reactions with electron-poor alkenes demonstrate good selectivity for the linear regioisomer, and the reactions with alkynes provide enone products with excellent selectivity for the E-isomers. The scope of the process was shown to be broad, tolerating a variety of substitution patterns and functional groups on both reaction components. A novel CN-directing effect was shown to be responsible for reversing the regioselectivity in a number of alkyne hydroacylation reactions. Catalyst loadings as low as 0.1 mol % were achievable.